Penyelesaian Sengketa Klaim Asuransi Kehilangan Kendaraan Bermotor pada Masa Kredit (Studi Kasus di PT. Capella Dinamik Nusantara Kabupaten Kampar) - Prayoga, Andi; Rianti, Ratna; Heriyanti, Yuli (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
There are two formulations of the problem, how to resolve a dispute on insurance claims for motorvechicles loss during the credit period at PT. Capella Dinamik Nusantara with what are the obstacles and obstacles in making insurance claims for insurance claim for motorized vehicles that are lost during the credit period, this study aims to detemine the settlement of insurance claims for loss of motorvehicles during the credit period at PT. Capella Dinamik Nusantara and to find out the obstacles and obstacles in making insurance claim for motorized vehicles that are lost during the credit period, this research method is a qualitative descrptive field research by taking a legal approach, namely the status approach, (case approach approach, historical approach(historical approach). The data used include statutory regulations as primary legal materials, books, journals, scientific publications as secondary materials, and dictionaries as teertiary legal materials.the results of the first study were based on an analysis conducted by comparing the laws and regulations, namely Law Number 40 Of 2014 Conceming Insurance, Article 246 of the KUHD, then with Law of Article 1 Paragraph (1) Number 8 of 1999 conceming Consumer Protection. Asuransi Astra Honda is required to pay the premium for claims submitted by the doctor, then mediation is carried out to obstacles in making insurance claims, the debtor’s lack of thoroughness in reading and understanding the contents of the initial agreement, which results in different interpretations, negligence in driving by the insured due to non-fulfillment of the requirements for motorized vehicle documents.